2020
DOI: 10.1088/2515-7647/ab7d81
|View full text |Cite
|
Sign up to set email alerts
|

High-order harmonic generation in a microfluidic glass device

Abstract: We report on the efficient generation of high-order harmonics in helium gas inside complex glass micro-devices fabricated by femtosecond laser micromachining. By exploiting the three-dimensional capabilities and extreme flexibility of this fabrication technique we developed fluidic micro-structures in a fused-silica substrate that allowed us to achieve accurate control of the gas density inside a micrometer-sized microchannel. As a result, we achieved a broadband spectrum of extreme ultraviolet (XUV) radiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 29 publications
(33 reference statements)
0
23
0
Order By: Relevance
“…The current literature of harmonic generation via nonlinear wave mixing is dominated by increasing the efficiency of the second/third harmonic generation rather than increasing the efficiency of an arbitrary harmonic . There are currently no known techniques in the literature that reported a high-efficiency in the microscale for an arbitrary harmonic generation (not necessarily the second harmonic) under monochromatic optical excitation [9][10][11][12][13][14][15][30][31][32][33][34][35][36][37][38][39]. In this study, we will show that for an arbitrary excitation frequency, one can maximize the harmonic generation efficiency at an arbitrary frequency.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…The current literature of harmonic generation via nonlinear wave mixing is dominated by increasing the efficiency of the second/third harmonic generation rather than increasing the efficiency of an arbitrary harmonic . There are currently no known techniques in the literature that reported a high-efficiency in the microscale for an arbitrary harmonic generation (not necessarily the second harmonic) under monochromatic optical excitation [9][10][11][12][13][14][15][30][31][32][33][34][35][36][37][38][39]. In this study, we will show that for an arbitrary excitation frequency, one can maximize the harmonic generation efficiency at an arbitrary frequency.…”
Section: Introductionmentioning
confidence: 80%
“…A computational study that is based on maximizing the harmonic generation efficiency via a nonlinear programming algorithm is lacking [ 6 , 7 , 8 ]. Experimental studies usually focus on finding new techniques to increase the second and the third harmonic generation efficiency and there are relatively few experimental studies that have demonstrated a minor increase in the harmonic generation or conversion efficiency via certain experimental configurations and setups [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. Some computational studies have focused on increasing the computation efficiency of harmonic generation problems rather than proving that the harmonic generation efficiency itself can actually be increased.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The integrated microfluidic glass device devoted to XUV generation by HHG in gas medium is composed [1] of a main micro-channel that works as a hollow-core waveguide (HCW) for the propagation of the femtosecond laser pulse. The interaction region is filled with the working gas using a micro-structured network of delivery channels fabricated in the same glass substrate.…”
Section: Introduction and Methodsmentioning
confidence: 99%
“…Here we present a De Laval conical nozzle realized on a fused-silica slab through Femtosecond Laser Irradiation followed by Chemical Etching (FLICE). The nozzle has been designed for application to High-order Harmonic Generation (HHG) [6] and ultrafast spectroscopy. In particular, it has been thought as a component of a more complex microfluidic FLICE device aiming at achieving gas density manipulation on the micronscale for efficient high-order harmonic generation on a chip [7].…”
Section: Introductionmentioning
confidence: 99%